2011
DOI: 10.1111/j.1365-3180.2011.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a decision support system for chemical control of annual ryegrass (Lolium rigidum) in winter cereals

Abstract: Field studies were conducted at five locations in North and East Spain to evaluate the agronomic, economic and environmental implications of a decision support system (LOLIUM-PC) for herbicide control of Lolium rigidum in winter cereals. The chemical control treatments evaluated were as follows: (i) LOLIUM-PC-based recommendations, (ii) full herbicide dose (standard farmer practice) and (iii) half herbicide dose. Results indicate that there were no statistically significant differences, within sites, between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Statistical coefficients of model performance showed that by using thermal time accumulation corrected for soil moisture, a reasonable predictive ability was achieved for a variety of geographic locations and soil types. Integrated into a multi‐year demographic model based on the complete annual life cycle of L. rigidum or into a decision support system for integrated management of this weed (González‐Andújar et al ., ), the model may contribute to help farmers decide on herbicide application time.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical coefficients of model performance showed that by using thermal time accumulation corrected for soil moisture, a reasonable predictive ability was achieved for a variety of geographic locations and soil types. Integrated into a multi‐year demographic model based on the complete annual life cycle of L. rigidum or into a decision support system for integrated management of this weed (González‐Andújar et al ., ), the model may contribute to help farmers decide on herbicide application time.…”
Section: Discussionmentioning
confidence: 99%
“…The models can easily be extended to allow the input of parameters related to the cost of each management, as well as potential grain yield losses due to the presence of Lolium plants. Another possibility is the incorporation of the likelihood of herbicide resistance into different management strategies, allowing future predictions of resistance evolution in the area [24] or be included in a decision support system to develop decision-making tools [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying extension paradigm is not new, this choice warrants explanations given the popularity of optimisation methods in agricultural DSS, especially for weed management (e.g. Neeser et al, 2004;Parsons et al, 2009;Gonzalez-Andujar et al, 2011).…”
Section: Addressing Learning Behaviour: Experimentation Vs Optimisationmentioning
confidence: 99%